Economic aspects of agricultural areas mangement and land/water ecotones conservation - Hans-Georg Petersen (Universität Potsdam, Lehrstuhl Finanzwissenschaft, 1995)
The task of writing a reliable and convincing paper on this topic is a very uneasy one because it is threefold: one has to know at least a bit about the agricultural sector, biology (or more precisely ecology), and about the sometimes beneficial but often distorting consequences of human activities. And all that has to be judged from the perspective of an economist who is aware of the steadily increasing uncertainties which are closely connected with post-modem sciences. Especially with regard to global, but also regional environmental issues, neither the conventional applied sciences nor the traditional professional consultancy deliver promising results. Today scientists have to tackle problems which are created by political necessities overwhelmingly caused by short-term human behavior, due in part to a serious lack of information on the longterm behavioral consequences. In these issues, typically, information stacks are high, scientific facts uncertain, individual as well as collective values disputed, and political decisions very urgent. In general, the post-normal situation is one where the traditional opposition of 'hard'facts and 'soft' values is inverted. Here we find decisions that are 'hard' in every sense, for which the scientific inputs are irremediably 'soft'.
urn:nbn:de:kobv:517-opus-15862
Keywords: 330